The Attractions of Agreement: Why Person Is Different - den Dikken, Marcel (Frontiers in Psychology, 2019)
This paper establishes the generalisation that whenever agreement with the finite verb is controlled by a constituent that is not in a Spec–Head relation with the inflectional head of the clause, this agreement cannot affect person. A syntactic representation for person inside the noun phrase and on the clausal spine is proposed which, in conjunction with the workings of agreement and concord, accommodates this empirical generalisation and derives Baker’s Structural Condition on Person Agreement (SCOPA). The proposal also provides an explanation for the φ-feature agreement facts of specificational copular sentences. The paper places its findings on person vs number agreement in the context of recent psycho- and neurolinguistic investigation of number/person dissociation.